Fat body-derived cytokine Upd2 controls disciplined migration of tracheal stem cells in Drosophila - Pengzhen Dong; Yue Li; Yuying Wang; Qiang Zhao; Tianfeng Lu; Jian Chen; Tianyu Guo; Jun Ma; Bing Yang; Honggang Wu; Hai Huang (eLife)
Coordinated activation and directional migration of adult stem cells are essential for maintaining tissue homeostasis. Drosophila tracheal progenitors are adult stem cells that migrate posteriorly along the dorsal trunk to replenish degenerating branches that disperse the fibroblast growth factor mitogen. However, it is currently unknown how the overall anterior-to-posterior directionality of such migration is controlled. Here, we show that individual progenitor cells migrate together in a concerted, disciplined manner, a behavior that is dependent on the neighboring fat body. We identify the fat body-derived cytokine, Upd2, in targeting and inducing JAK/STAT signaling in tracheal progenitors to maintain their directional migration. Perturbation of either Upd2 production in fat body or JAK/STAT signaling in trachea causes aberrant bidirectional migration of tracheal progenitors. We show that JAK/STAT signaling promotes the expression of genes involved in planar cell polarity leading to asymmetric localization of Fat in progenitor cells. We provide evidence that Upd2 transport requires Rab5- and Rab7-mediated endocytic sorting and Lbm-dependent vesicle trafficking. Our study thus uncovers an inter-organ communication in the control of disciplined migration of tracheal progenitor cells, a process that requires vesicular trafficking of fat body-derived cytokine Upd2 and JAK/STAT signaling-mediated activation of PCP genes.